SELECTIVE INVISIBILITY AND THE REVERSE OF DIGNITY: A STUDY ON MODERN SLAVERY AND RACISM IN BRAZIL FROM THE PERSPECTIVE OF DECENT WORK - Guimarães, Emilly de Jesus Ferreira; Lage, Mariana Gonçalves Pires; Tonacio, Claudia Michelly Sales de Paiva (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2025)
This study, from a dialectical perspective, investigates the intersection between modern slavery and racism, examining how this connection perpetuates social invisibility and marginalization. The research problem centers on the persistence of contemporary slave labor despite legal frameworks prohibiting it, with a specific focus on its disproportionate impact on racialized populations. The study aims to analyze the structural and historical dimensions that link forced labor to systemic racism, assessing their implications for human dignity and social exclusion. Methodologically, the research employs a multidisciplinary approach, integrating legal, historical, and sociological analyses with empirical data on contemporary cases of forced labor in Brazil. The findings demonstrate that modern slavery is deeply embedded in racist practices, reinforcing cycles of vulnerability and systematic violations of fundamental rights. The study highlights how institutional mechanisms and economic exploitation sustain these inequalities, making eradication efforts insufficient without addressing the racialized nature of labor exploitation. The originality of this study lies in its comprehensive examination of modern slavery through the lens of structural racism, providing a critical perspective on how historical legacies shape contemporary labor relations. Its value stems from its contribution to the broader discourse on human rights, social justice, and labor policies, offering insights for more effective legal and social interventions aimed at eliminating modern forms of slavery.